Waqf concept health clinic – “Uniqueness in disguise” USIM experience - Fathima Begum Syed Mohideen1; Mohd Radzniwan A Rashid; Sharifah Najwa Syed Mohamad; Zuhairiah Mohamad; Muhammad Shamsir Bin Mohd Aris; Jaafar, Azlan (Malaysian Journal of Science Health & Technology, 2021)
Waqf or religious endowment is of a benevolence instrument emerged to help reduce the burden of the disadvantaged people. As the cost for medical expenses are exorbitant, the availability of waqf should contribute to the improvement of the community health. The establishment of Universiti Sains Islam Malaysia (USIM) Specialist healthcare clinic was founded by the idea of waqf through healthcare for the less fortunate. With collaboration from many agencies the establishment of the clinic has served community in need to access better health care. The primary aim of waqf clinic establishment is to continually uphold the Islamic aspects in its establishment and management for betterment of health among disadvantaged people.